2013
DOI: 10.1099/ijs.0.037432-0
|View full text |Cite
|
Sign up to set email alerts
|

Halobaculum magnesiiphilum sp. nov., a magnesium-dependent haloarchaeon isolated from commercial salt

Abstract: Two extremely halophilic archaea, strains MGY-184 T and MGY-205, were isolated from sea salt produced in Japan and rock salt imported from Bolivia, respectively. Both strains were pleomorphic, non-motile, Gram-negative and required more than 5 % (w/v) NaCl for growth, with optimum at 9-12 %, in the presence of 2 % (w/v) MgCl 2 . 6H 2 O. In the presence of 18 % (w/v) MgCl 2 . 6H 2 O, however, both strains showed growth even at 1.0 % (w/v) NaCl. Both strains possessed two 16S rRNA genes (rrnA and rrnB), and they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…2000) and their optimum growth was reported to be 10–30°C (Shimoshige et al . 2013). Therefore, it is commonly assumed that the family Halobacteriaceae is inhabiting extreme habitat, but molecular data indicated the presence of archaea in moderate environments, such as seawater.…”
Section: Resultsmentioning
confidence: 99%
“…2000) and their optimum growth was reported to be 10–30°C (Shimoshige et al . 2013). Therefore, it is commonly assumed that the family Halobacteriaceae is inhabiting extreme habitat, but molecular data indicated the presence of archaea in moderate environments, such as seawater.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a slight (even if poor) growth of the strain was even reported at 17.14% (1.8 M) MgCl 2 . There are several examples of haloarchaeal strains that require high concentrations of magnesium for their growth in the literature, including Halobacterium salinarum DSM 3754 T , Halobaculum gomorrense DS2807 T , Haloferax volcanii DS2 T and Halobaculum magnesiiphilum MGY-184 T (Mullakhanbhai and Larsen, 1975; Oren et al, 1995; Grant, 2001; Shimoshige et al, 2013). For instance, authors reported that H. magnesiiphilum is able to grow in media with 30% (1.48M) MgCl 2 .6H 2 O (Shimoshige et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although salt had been known only to restrain the growth of food-poisoning bacteria and to promote the growth of fermentating bacteria such as yeast and lactic acid bacteria, new types of halophilic archaea are recently being identified in fermented food products with high salt concentration ( Table 1). The existence of halophilic archaea in salted foods may be due to salterns being one of the important environments for their growth, so salt produced from these salterns would contain haloarchaea [23,53,55]. Among fermented foods, new types of halophilic archaea have been discovered in fermented fish and fish sauces that require a large amount of salt, and such studies are being conducted mostly in Korea, Japan, and Southeast Asian countries, despite the fact that various types of fermented fish and shellfish products are present worldwide.…”
Section: Halophilic Archaea In Foods Identified By Culture-dependent mentioning
confidence: 99%
“…The fact that halophilic archaea are still alive in salts after being heated by the sun in salterns and dried for at least 10 days suggests that the chances for halophilic archaea to come in contact with humans are much higher than expected. Halophilic archaea that have been isolated and identified from Japanese commercial salts include Salarchaeum japonicum [53], Halobaculum magnesiiphilum [55], Natronoarchaeum mannanilyticum [54], Halarchaeum acidiphilum [26], and Halostagnicola alkaliphila [30], and these halophilic archaea show a much wider variety of growth conditions compared with those isolated from high salt-fermented foods. Whereas most halophilic archaea are mesophilic, Halobaculum magnesiiphilum [55] can grow in temperatures up to 55 o C (optimal growth temperature is 45 o C), and it also grows in 30% (w/v) MgCl 2 concentration since it is magnesiumdependent.…”
Section: Halophilic Archaea In Foods Outside Koreamentioning
confidence: 99%